Improving Classroom Management Skills Through Micro Teaching for Pre-Service Teachers of Vocational Schools - Padilah, Dede; Berman, Ega Taqwali; Solehudin, Agus (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Classroom management is vital for fostering productive learning environments. As a leading teacher-training institution, Universitas Pendidikan Indonesia (UPI) employs microteaching to equip students with pedagogical skills. This qualitative case study examines how microteaching enhances classroom management competencies among six Mechanical Engineering Education students, preparing them for the Program Penguatan Profesional Kependidikan (P3K). Data were collected through interviews on microteaching implementation, classroom management practices, and observations of teaching sessions. Supporting documentation and triangulation ensured validity. Analysis followed stages of reduction, presentation, and conclusion. Findings indicate that structured microteaching significantly improves classroom management abilities, evident in students' enhanced performance during school-based teaching. The program's procedural adherence enables participants to refine lesson delivery, behavioural management, and instructional adaptability. Practical experience through microteaching not only bridges theoretical knowledge with real-world application but also builds confidence and readiness for first aid challenges. Thus, microteaching is a critical preparatory tool, equipping future educators with the skills to navigate dynamic classroom settings and meet professional demands. These outcomes underscore the value of experiential training in teacher education, positioning UPI's approach as a model for cultivating adaptable, classroom-ready educators.